2011
DOI: 10.3138/jcfs.42.4.579
|View full text |Cite
|
Sign up to set email alerts
|

The Intersection of Motherhood and Disability: Being a “Good” Korean Mother to an “Imperfect” Child

Abstract: This study springs from a larger cross-cultural project about mothering a child with a disability in South Korea and in the United States. The present analysis focuses on data collected in South Korea. Integrating critical feminist and disability theories within a social constructionist framework (McGraw & Walker, 2007), we asked (a) how dominant sociocultural systems related to mothering and disability shape South Korean mothers’ understanding of themselves and their children with autism and (b) how mothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 28 publications
0
14
1
Order By: Relevance
“…of Motherhood (1974) whereas women engaged in the majority of labor, much to their detriment and men’s benefit. Several JB papers examined disparate division of household and parenting tasks within heterosexual couples, even if it was not the main focus, including Kibria (1990); Fassinger, (1993); Gosling and Zengari (1996); Pyke (1996); Haddock et al (2000), You and McGraw (2011), and Yavorsky et al (2015). Egalitarian relationships are not the norm in practice; although recent research has shown increases in shared experiences, the long-standing pattern of women doing more housework and childcare persists (Horne et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…of Motherhood (1974) whereas women engaged in the majority of labor, much to their detriment and men’s benefit. Several JB papers examined disparate division of household and parenting tasks within heterosexual couples, even if it was not the main focus, including Kibria (1990); Fassinger, (1993); Gosling and Zengari (1996); Pyke (1996); Haddock et al (2000), You and McGraw (2011), and Yavorsky et al (2015). Egalitarian relationships are not the norm in practice; although recent research has shown increases in shared experiences, the long-standing pattern of women doing more housework and childcare persists (Horne et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Examining ideologies of motherhood within diverse cultural contexts, the collection of JB papers extends Bernard’s initial theorizing. Four papers in the collection (i.e., Berkowitz, 2011; Edwards & Few-Demo, 2016; Goldberg & Allen, 2007; You & McGraw 2011) focus on the construction and/or performance of motherhood. Goldberg and Allen (2007) drew on interviews with 60 lesbian women transitioning to parenthood.…”
Section: Resultsmentioning
confidence: 99%
“…There is a stigma that is so strong in this country that many doctors Koreans deliberately misdiagnose these children with aechak changae, or reactive detachment withdraw from social disorder-caused by the extreme neglect or abuse by parents. In South Korea, individuals with all types of individuals who experience disabilities have stigmatized and seen as a threat to family [48]. Description of the development of disabled individuals who have limitations because of the population and the media may be seen as violent, dangerous and depressing [49].…”
Section: Cultural Views About Autismmentioning
confidence: 99%
“…The immigrants are also defined by the roles they play as mother, wife, and daughter‐in‐law. For example, the social standing of marriage‐labor immigrants in Korea is closely associated with their “successful mothering.” This is because children's success in assimilating to the dominant culture is seen as an important indicator of the parents’ performance (You and McGraw ).…”
Section: Marriage‐labor Immigrant Mothers and Their Cultural Labormentioning
confidence: 99%